A critical review of design and fabrication challenges in InP HEMTs for future terahertz frequency applications. (15th June 2021) - Ajayan, J.; Nirmal, D.; Mathew, Ribu; Kurian, Dheena; Mohankumar, P.; Arivazhagan, L.; Ajitha, D.
Abstract: This article critically reviews the materials, processing and reliability of InP high electron mobility transistors (InP HEMTs) for future terahertz wave applications. The factors such as drain current (ID ) over 1200 mA/mm, transconductance (gm ) over 3000 mS/mm, cut off frequency (fT ) over 700 GHz and maximum oscillation frequency (fmax ) over 1300 GHz makes InP HEMTs suitable for Terahertz wave applications. Furthermore, low DC power consumption and outstanding low noise performance makes InP HEMT most appropriate transistor technology for the development of space based receivers. This review article critically assesses the challenges in miniaturization of InP HEMTs, doping strategies in InP HEMTs, buried platinum technology, impact of annealing process and temperature, influence of electron and proton irradiation, thermal and bias stress on the reliability of InP HEMTs, cavity and gating effects and influence of trapping effects. InP HEMTs are very much preferable in applications like radio astronomy, terahertz optical and wireless communication systems, atmospheric imaging and sensing, automotive radar, ground based receivers in deep space networks, terahertz imaging and sensing, biomedical applications, security screening, video conferencing & real time multimedia file transfer, high speed and ultra low power digital integrated circuits.